The Nexus Between Remittances and Financial Inclusion: A Systematic Review by Prisma Method - BOUDRI HAJAR; ISMAILI IDRISSI BOUTAINA (African Scientific Journal, 2025)
Abstract Workers’ remittances represent a crucial source of financing for recipient countries, often surpassing foreign direct investment (FDI) inflows (Sirkeci, Ratha, Cohen, 2012). International remittances to emerging economies have gained increasing importance due to their substantial volume, role in financial markets and broader economic and social impacts (Ismaili Idrissi, 2023). Interest in migrant remittances and financial inclusion has grown since the 1990s, in line with the boom in international migration. These financial flows have helped to increase access to financial services, particularly in developing countries. This has prompted the development of public and international policies to support them. However, the relationship between remittances and financial inclusion is complex and multidimensional. This paper assesses the evidence on the link between financial inclusion and remittances using the PRISMA method. This review employs a rigorous search strategy, combining PRISMA criteria with bibliographic linkage techniques to identify, select and critically analyze relevant studies. The analysis covers publications from 2019 to 2024 in both French and English, focusing primarily on journals indexed in Web of Science, Scopus, and Google Scholar. The methodology integrates two complementary approaches: a descriptive analysis and a thematic analysis. The descriptive analysis uses frequency tables and univariate statistics to outline the characteristics of the selected studies, while the thematic analysis conducts a lexical examination based on word frequency, in order to identify key concepts in the research. The PRISMA method utilizes two software tools- Nvivo 12 and the IBM SPSS Statistics 27- to visualize scientific trends. Finally, the paper proposes future research directions on migrant remittances and their impact on financial inclusion. Key words : Financial inclusion, financial institutions, Government policy and regulation, Migrant remittances, PRISMA.